fatorar o trinomio Y=x²+x-6
Soluções para a tarefa
Respondido por
2
Aplicando bhaskara vc encontra as raízes x= -3 e x=2, logo
y = (x+3)(x-2)
Respondido por
7
Y = x² + x - 6
x² + x - 6 = 0
x' = -1 - 5 / 2
x' = -6/2
x' = -3
x'' = -1 + 5 / 2
x'' = 4/2
x'' = 2
S = {-3, 2}
===
x' = -3
x + 3 = 0
x''= 2
x - 2 = 0
y = (x + 3).(x - 2)
x² + x - 6 = 0
x' = -1 - 5 / 2
x' = -6/2
x' = -3
x'' = -1 + 5 / 2
x'' = 4/2
x'' = 2
S = {-3, 2}
===
x' = -3
x + 3 = 0
x''= 2
x - 2 = 0
y = (x + 3).(x - 2)
Perguntas interessantes
Inglês,
1 ano atrás
Português,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás